Fenomenologi pembelajaran personal berbasis komunitas untuk pendidikan karakter - Luthfi Audia Pribadi; Dedy Achmad Kurniady; Suryadi Suryadi; Nugraha Suharto (Universitas Pendidikan Indonesia, 2026)
This research stems from the need for a learning model that not only emphasizes cognitive aspects but also integrates affective, moral, and spiritual dimensions holistically. This study aims to examine the personalized learning model through the Movement Community in Komunitas Musisi Mengaji (Komuji) to strengthen character education within values- and community-based education. The research employed a qualitative, phenomenological approach. Data were collected through in-depth interviews, participant observation, and documentation of community activities, and were then analyzed thematically. The results show that Komuji functions as a personalized, community-based learning space in which character values such as integrity, empathy, responsibility, discipline, and spirituality are internalized through collaborative activities, including mentoring, reflection on values, and social projects. The learning process is reflective, relational, and existential, fostering students' self-awareness and intrinsic motivation for moral behavior. This research contributes to the development of the Community-Based Personalized Character Learning (CBPCL) model, which emphasizes that personalized learning can be achieved collectively through meaningful community interactions and offers practical implications for educators and curriculum developers in designing learning strategies that are contextual, humanistic, and rooted in life values.